Factors associated with use of falls risk–increasing drugs among patients of a geriatric oncology outpatient clinic in Australia: a cross‐sectional study†. Issue 2 (24th August 2016) - Turner, Justin P.; Tervonen, Hanna E.; Shakib, Sepehr; Singhal, Nimit; Prowse, Robert; Bell, J. Simon
Abstract: Older people with cancer are at increased risk of falling. Falls risk–increasing drugs (FRIDs), comprising psychotropics and medications that cause orthostatic hypotension, are a potentially modifiable risk factor for falls. The objective of this study was to determine the prevalence and factors associated with use of FRIDs in older people with cancer. Patients aged ≥70 years who presented to a hospital outpatient clinic between January 2009 and July 2010 were included in the study. Information on current medication use, falls in previous 6 months, and frailty criteria was collected. Multinomial logistic regression was used to compute odds ratios (OR) and 95% confidence intervals (CIs) for factors associated with levels of FRID use. Overall, 76.1% (n = 293) of 383 patients used FRIDs. This comprised psychotropics (31.2%, n = 120) and medications causing orthostatic hypotension (69.9%, n = 269). In total, 24.0% (n = 92) patients reported falling in the previous 6 months. Risk factors for falling were associated with use of psychotropics but not orthostatic hypotension drugs. Patients with a history of falls had increased odds of using psychotropics (≥3 psychotropics; OR 13.50; 95%CI, 2.64‐68.94). Likewise, frail patients had increased odds of using psychotropics (≥3 psychotropics; OR 27.78; 95%CI, 6.06‐127.42). Risk factors for falling were associated with the use of psychotropics. This suggests that clinicians either do not recognize or underestimate the contribution of medications to falls in this high‐risk patient group. Further efforts are needed to rationalize medication regimens at the time of patients' first presentation to outpatient oncology services.